2012
DOI: 10.1111/j.1365-2923.2012.04265.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparities in undergraduate pre‐clinical and clinical performance

Abstract: Strong ethnic disparities exist in medical school performance even after adjusting for age, gender, pu-GPA and socio-demographic variables. More subjective grading cannot be ruled out as a cause of lower grades in clinical training, but other possible explanations should be studied further to mitigate the disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 33 publications
4
74
1
Order By: Relevance
“…Within clinical placements the judgement of educators has been studied with concerns over overt negative bias noted in both physiotherapy [12,13] and medicine [16,17]. Feelings of isolation and hostility in the academic environment have also been noted [9].…”
Section: Discussionmentioning
confidence: 99%
“…Within clinical placements the judgement of educators has been studied with concerns over overt negative bias noted in both physiotherapy [12,13] and medicine [16,17]. Feelings of isolation and hostility in the academic environment have also been noted [9].…”
Section: Discussionmentioning
confidence: 99%
“…Questions about the ethnic background of the students pertaining to the country of birth of the student and parents and the language spoken with parents were included in the survey (Stegers-Jager et al 2012b). Ethnic minority was defined according to the Statistics Bureau of the Netherlands (CBS, www.cbs.nl) as “a person with at least one parent born outside the Netherlands.” The classification of ethnic minorities in five groups was also in alignment with CBS: “Turkish/Moroccan/African, Surinamese/Antillean, Asian (including Chinese), Western (including European, North American and Oceanian, Indonesian, and Japanese), and Other” (Stegers-Jager et al 2012b).…”
Section: Methodsmentioning
confidence: 99%
“…Studies from Australia and the Netherlands show that they underperform in the first year of medical school (Kay-Lambkin et al 2002; Stegers-Jager et al 2012) and also later in the course, in final year assessments in Australia, the UK and the USA (Liddell and Koritsas 2004; McManus et al 1996; Xu et al 1993). A systematic review and meta-analysis showed that ethnic minority students in the UK academically underperform compared with white students throughout medical school and across different types of examinations (Woolf et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Others found that they received lower grades in their clerkships (Lee et al 2007; Stegers-Jager et al 2012). The underperformance in clinical assessments of ethnic minority students was also found among physiotherapy students (Naylor et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation